An ISM approach for modelling the variables affecting the selection of material handling equipments in advance manufacturing system. (2015) - Kumar, Surinder; Raj, Tilak
This paper presents the application of interpretive structural modelling (ISM) approach for modelling the variables of automated material handling systems as a useful tool in advanced manufacturing system. There are certain variables, which help in the implementation of material handling systems in advance manufacturing systems. These variables affect these material handling systems and influence one another also. The main objective of this paper is to understand the mutual interaction of these variables and to identify the 'driving variables' and the 'dependent variables'. In the present work, these variables have been identified through the literature survey and their ranking is done by a questionnaire-based survey. The ISM approach has been utilised in analysing their mutual interaction and in preparation of a model through which some key variables can be identified for the implementation of automated material handling systems (AMHS).